Measurements of the Λ0b→J/ψΛ decay amplitudes and the Λ0b polarisation in pp collisions at √s=7 TeV - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physics letters, 2013)
An angular analysis of Λb0→J/ψΛ decays is performed using a data sample corresponding to 1.0 fb−1 collected in pp collisions at s=7 TeV with the LHCb detector at the LHC. A parity violating asymmetry parameter characterising the Λb0→J/ψΛ decay of 0.05±0.17±0.07 and a Λb0 transverse production polarisation of 0.06±0.07±0.02 are measured, where the first uncertainty is statistical and the second systematic.